The reliability of cone-beam computed tomography to assess bone density at dental implant recipient sites: a histomorphometric analysis by micro-CT - González-García, Raúl; Monje, Florencio (Clinical oral implants research, 2013)
Objectives The aim of this study was to objectively assess the reliability of the cone‐beam computed tomography (CBCT) as a tool to pre‐operatively determine radiographic bone density (RBD) by the density values provided by the system, analyzing its relationship with histomorphometric bone density expressed as bone volumetric fraction (BV/TV) assessed by micro‐CT of bone biopsies at the site of insertion of dental implants in the maxillary bones. Material and methods Thirty‐nine bone biopsies of the maxillary bones at the sites of 39 dental implants from 31 edentulous healthy patients were analyzed. The NobelGuide™ software was used for implant planning, which also allowed fabrication of individual stereolithographic surgical guides. The analysis of CBCT images allowed pre‐operative determination of mean density values of implant recipient sites along the major axis of the planned implants (axial RBD). Stereolithographic surgical guides were used to guide implant insertion and also to extract cylindrical bone biopsies from the core of the exact implant site. Further analysis of several osseous micro‐structural variables including BV/TV was performed by micro‐CT of the extracted bone biopsies. Results Mean axial RBD was 478 ± 212 (range: 144–953). A statistically significant difference (P = 0.02) was observed among density values of the cortical bone of the upper maxilla and mandible. A high positive Pearson's correlation coefficient (r = 0.858, P < 0.001) was observed between RBD and BV/TV, with the regression equations: (1) Axial RBD = −19.974 + 10.238·BV/TV; (2) BV/TV = 14.258 + 0.72·Axial RBD. RBD was also positively correlated with the trabecular thickness (Tb.Th) and trabecular number (Tb.N), but negatively correlated with trabecular separation (Tb.Sp), structural model index, and inverse connectivity (Tb.Pf). Density values upper than 450 were associated with BV/TV upper than 50%, mean Tb.Th upper than 0.2 mm, mean Tb.Sp lower than 0.3 mm, and mean Tb.N upper than 2. Conclusion RBD assessed by CBCT has a strong positive correlation with BV/TV assessed by micro‐CT at the site of dental implants in the maxillary bones. Pre‐operative estimation of density values by CBCT is a reliable tool to objectively determine bone density.